Bilateral simultaneous acute angle closure caused by sulphonamide derivatives: A case series - Senthil, Sirisha (Medknow Publications, 2010)
The sulphonamide group of drugs is implicated in bilateral acute angle closure (AAC) due to an idiosyncratic response. We report a series of three cases with bilateral AAC caused by different sulphonamide derivatives, their presentation and management.